Waning Time of Maternally Derived Anti-Hepatitis A and Anti-Varicella Zoster Virus Antibodies - Guzelkucuk, Zeliha; Duyan Camurdan, Aysu; Beyazova, Ufuk; Bozdayı, Gulendam; Civil, Fusun; Altay Kocak, Aylin (Journal of Pediatric Infectious Diseases, 2019)
Objective The objective of this study was to investigate the persistence of maternally derived antibodies to hepatitis A (anti-HAV) and varicella zoster (anti-VZV) viruses to determine the optimal time of vaccination of infants.Materials and Methods This study was conducted between 2011 and 2012 at the Gazi University Hospital. Blood samples were collected from healthy infants' cord blood and at 12th, 18th, and 24th months of age. Anti-HAV and anti-VZV immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies were measured by enzyme-linked immunosorbent assay kit in blood samples.Results A total of 546 infants and children were included in the study; all had blood samples taken at four time points (at birth [cord blood], and at 12, 18, and 24 months). Anti-HAV IgG seropositivity rates in these samples were 77.3, 29.6, 14.8, and 17.7%, respectively (p < 0.05). Corresponding anti-VZV IgG seropositivity rates were 83.3, 21.5, 29.5, and 33.8%, respectively (p < 0.05).Conclusion Anti-HAV and anti-VZV seropositivity rates were lowest at 18 and 12 months, respectively. We suggest that if VZV and hepatitis A vaccines were included in the national vaccination program after the age of 1 year, there should be little interference from passively acquired maternal antibodies.
Keywords: maternally derived antibody; hepatitis A; varicella zoster; vaccine